Expression signature of lncRNAs and their potential roles in cardiac fibrosis of post-infarct mice. Issue 3 (3rd June 2016) - Qu, Xuefeng; Song, Xiaotong; Yuan, Wei; Shu, You; Wang, Yuying; Zhao, Xuyun; Gao, Ming; Lu, Renzhong; Luo, Shenjian; Zhao, Wei; Zhang, Yue; Sun, Lihua; et al.
Abstract : Myocardial fibrotic tissue from mouse infarcted heart displayed the expression signature of long non-coding RNAs (lncRNAs) and mRNAs. Fifty-seven differentially expressed lncRNAs and 20 differentially expressed mRNAs were found to be related to 8 signalling pathways involved in the development of cardiac fibrosis. Abstract : The present study aimed to investigate whether long non-coding RNAs (lncRNAs) are involved in cardiac fibrogenesis induced by myocardial infarction (MI). The differentially expressed lncRNAs and mRNAs in peri-infarct region of mice 4 weeks after MI were selected for bioinformatic analysis including gene ontology (GO) enrichment, pathway and network analysis. Left ventricular tissue levels of lncRNAs and mRNAs were compared between MI and sham control mice, using a false discovery rate (FDR) of <5%. Out of 55000 lncRNAs detected, 263 were significantly up-regulated and 282 down-regulated. Out of 23000 mRNAs detected, 142 were significantly up-regulated and 67 down-regulated. Among the differentially expressed lncRNAs, 53 were up-regulated by ≥2.0-fold change and 37 down-regulated by ≤0.5-fold change. Nine up-regulated and five down-regulated lncRNAs were randomly selected for quantitative real-time PCR (qRT-PCR) verification. GO and pathway analyses revealed 173 correlated lncRNA–mRNA pairs for 57 differentially expressed lncRNAs and 20 differentially expressed genes which are related to the development of cardiac fibrosis. We identified TGF-β3 as the top-ranked gene, a critical component of the transforming growth factor-β (TGF-β) and mitogen activated protein kinase (MAPK) signalling pathways in cardiac fibrosis. NONMMUT022554 was identified as the top-ranked lncRNA, positively correlated with six up-regulated genes, which are involved in the extracellular matrix (ECM)–receptor interactions and the phosphoinositid-3 kinase/protein kinase B (PI3K-Akt) signalling pathway. Our study has identified the expression signature of lncRNAs in cardiac fibrosis induced by MI and unravelled the possible involvement of the deregulated lncRNAs in cardiac fibrosis and the associated pathological processes.